Desafíos para la implementación de una pólitica pública de protección integral a los niños de la Fundación Juvilus - Moran Velasco, Mayvelline Odalys (2025)
HIV, a disease that affects the immune system, continues to represent a global challenge. However, advances in antiretroviral treatments have significantly improved the quality of life of infected children. The Juvilus Foundation, dedicated to supporting orphaned children affected by HIV, faces serious problems related to financing and social support, which highlights the need to guarantee economic and medical protection and the safeguarding of the fundamental rights of these minors in vulnerable situations. Therefore, the central purpose of this research was to address the challenges associated with the implementation of a public policy aimed at comprehensively protecting the children of the Juvilus Foundation. Through a qualitative approach and a non-experimental design, it was analyzed how the lack of a specific public policy can transcend to not adequately protecting the rights of children and adolescents. A cross-sectional study was carried out complemented with analytical-synthetic, historical-logical and dogmatic-legal methods, as well as with direct observation and semistructured interviews applied to a non-probabilistic sample. The findings therefore underline that public policies are essential to safeguard the rights of children living with HIV, in this regard, and by providing key guidelines for their well-being. However, the effectiveness of these policies depends largely on their correct implementation, and the best interest of the child was identified as a principle that seeks to guarantee the rights of children and ensure that they are effectively fulfilled.